2014
DOI: 10.1007/s10549-014-3232-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay and Nb2 lymphoma bioassay prolactin levels and mammographic density in premenopausal and postmenopausal women the Nurses’ Health Studies

Abstract: Background Higher circulating prolactin levels have been associated with higher percent mammographic density among postmenopausal women in some, but not all studies. However, few studies have examined associations with dense area and non-dense breast area breast or considered associations with prolactin Nb2 lymphoma cell bioassay levels. Methods We conducted a cross-sectional study among 1124 premenopausal and 890 postmenopausal women who were controls in breast cancer case-control studies nested in the Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…Details of mammographic density measurement were described elsewhere (33). Briefly, a Lumysis 85 laser film scanner was used to digitize the craniocaudal views of both breasts for all mammograms in the NHS and for the first two batches of mammograms in the NHSII.…”
Section: Mammographic Density Measurementmentioning
confidence: 99%
“…Details of mammographic density measurement were described elsewhere (33). Briefly, a Lumysis 85 laser film scanner was used to digitize the craniocaudal views of both breasts for all mammograms in the NHS and for the first two batches of mammograms in the NHSII.…”
Section: Mammographic Density Measurementmentioning
confidence: 99%
“…In humans, prolactin is primarily produced in the anterior pituitary gland, but it is also expressed in the mammary gland itself and adipose tissue, among others [ 49 ]. In postmenopausal women, higher prolactin levels have been associated with higher mammographic density in three studies [ 50 52 ], two other studies found no association [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these high within-person intraclass correlation coefficients, between-batch variability was present in the NHSII. Batch adjustment methods were applied to the second and third NHSII batch measurements to reflect the density measurements had they been evaluated in the first batch [ 26 , 29 ]. The primary outcome of interest was percent mammographic density (i.e., the dense area divided by the total breast area), and secondary outcomes of interest included absolute dense area (cm 2 ) and absolute nondense area (cm 2 ).…”
Section: Methodsmentioning
confidence: 99%